2018
DOI: 10.3389/fnbeh.2018.00045
|View full text |Cite
|
Sign up to set email alerts
|

Writing About Past Failures Attenuates Cortisol Responses and Sustained Attention Deficits Following Psychosocial Stress

Abstract: Acute stress can harm performance. Paradoxically, writing about stressful events—such as past failures—has been shown to improve cognitive functioning and performance, especially in tasks that require sustained attention. Yet, there is little physiological evidence for whether writing about past failures or other negative events improves performance by reducing stress. In this experiment, we studied the effects of an acute psychosocial stressor, the Trier Social Stress Test, on attentional performance and sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Resilience was significantly associated with acute cortisol response and/or recovery from momentary stressors in six out of the 11 studies that reported on this relationship, with the nature of the association between these two variables being primarily negative (Lau et al, 2021; Mikolajczak et al, 2008; Ruiz‐Robledillo et al, 2017; Sun et al, 2014), but also, in some cases, positive (DiMenichi et al, 2018) or mixed (Park et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Resilience was significantly associated with acute cortisol response and/or recovery from momentary stressors in six out of the 11 studies that reported on this relationship, with the nature of the association between these two variables being primarily negative (Lau et al, 2021; Mikolajczak et al, 2008; Ruiz‐Robledillo et al, 2017; Sun et al, 2014), but also, in some cases, positive (DiMenichi et al, 2018) or mixed (Park et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Much of the work on the benefits of expressive writing has focused on how writing about very negative experiences, such as trauma, provides emotional benefits (Pennebaker et al, 1988; Harber and Pennebaker, 1992; Lepore and Smyth, 2002; Smyth et al, 2008). However, there is also evidence that writing about more universally experienced negative events and emotions, such as test anxiety and failure, confers benefits as well (Klein and Boals, 2001; Ramirez and Beilock, 2011; DiMenichi and Richmond, 2015; DiMenichi et al, 2018). Our neural results show that expressive writing about commonplace negative events, such as failure, leads to differences in neural processes during cognitive tasks similar to those encountered in school environments, such as memory tasks.…”
Section: Discussionmentioning
confidence: 99%
“…For example, writing about a past trauma has led to reductions in anxiety and depression (Lepore and Smyth, 2002; Smyth et al, 2008), as well as improvements in physical health (Pennebaker et al, 1988; Harber and Pennebaker, 1992). Writing about anxieties has also resulted in improved cognitive performance, both in the laboratory (Klein and Boals, 2001; DiMenichi and Richmond, 2015; DiMenichi et al, 2018) as well as in the classroom on high stakes exams (Ramirez and Beilock, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations